2011
DOI: 10.1016/j.polymertesting.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of a compression test device for investigating interaction between diffusion of biodiesel and large deformation in rubber

Abstract: International audienceMotivated by environmental and economic factors, biodiesel has been introduced to partially replace the diminishing stock of petroleum-based fuel. However, the use of biodiesel such as palm biodiesel is placing additional demands on automotive components, e.g. rubber components, due to a compatibility issue in the fuel system. In engineering applications where hostile environments are involved, the long-term mechanical response of rubber components is affected by interactions existed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Furthermore, the only effect of swelling is to reduce the modulus in inverse proportion to the cube root of the swelling degree without changing the form of the stress-strain curves. Nevertheless, as shown in our previous work (Chai et al, 2011), deviation of Treolar's theory was observed. Hence, following Durning and Morman (1993), we postulate the following form ofŴ J s :…”
Section: Extension Of Classical Modelssupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, the only effect of swelling is to reduce the modulus in inverse proportion to the cube root of the swelling degree without changing the form of the stress-strain curves. Nevertheless, as shown in our previous work (Chai et al, 2011), deviation of Treolar's theory was observed. Hence, following Durning and Morman (1993), we postulate the following form ofŴ J s :…”
Section: Extension Of Classical Modelssupporting
confidence: 58%
“…No standard is followed regarding the choice of the specimens and immersion durations. The detailed features of the specimen and chemical compositions of the palm biodiesel used in the present study are provided in our previous works (Chai, Andriyana, Verron, Johan, & Haseeb, 2011;Ch'ng, Andriyana, Verron, Kahbasi, & Ahmad, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chai et al 4 designed a compression device to evaluate the durability of industrial rubber components exposed to an aggressive environment, for example, oil in a biofuel system during their service. The apparatus was made up of four rectangular stainless steel plates with spacer bars in between, and thus, precompression was introduced for the rubber specimens while they were immersed into diesel.…”
Section: Trakarnpruk and Porntangjitlikitmentioning
confidence: 99%
“…Nevertheless, this level of strain is retained to represent initially stress-free condition while ensuring that the diffusion occurs only along radial direction. The details about the compression device is given in Chai et al (2011).…”
Section: Specimen Geometry and Compression Devicementioning
confidence: 99%